Insertion and follow-up of complete dentures: a literature review - Goiato, Marcelo Coelho [UNESP]; Genneri Filho, Humberto; Santos, Daniela Micheline dos [UNESP]; Ricardo Barao, Valentim Adelino; Freitas Junior, Amilcar Chagas (Wiley-Blackwell, 2011)
Insertion and follow-up of complete dentures: a literature reviewObjective: The aim of this study was to present the importance of clinical procedures related to insertion and follow-up of complete dentures in elderly patients.Materials and Methods: The success of rehabilitation with complete dentures results from the accuracy of clinical and laboratorial procedures that makes the denture insertion an important step of treatment.Conclusion: The follow-up and professional maintenance of function and hygiene facilitates long-term efficiency.
Keywords: elderly; complete denture; denture insertion; patient follow-up